The social geography of fear and acceptance: an interview study on attitudes toward LGBQ identities in residential aged care - Klara Le (BMC Geriatrics)
Abstract Background Older LGBQ (lesbian, gay, bisexual and queer/questioning) adults in residential aged care (RAC) navigate environments shaped by heteronormative norms, institutional structures, and the social dynamics of communal living. Unlike in private homes, RAC settings bring together individuals with diverse backgrounds, values, and attitudes, creating both opportunities for inclusion and risks of exclusion. This study examines how both LGBQ and non-LGBQ residents contribute to shaping the social and cultural conditions of RAC and how these dynamics influence older LGBQ adults’ ability to express their sexual identity. Methods This study employed a qualitative approach, conducting semi-structured interviews with 17 residents aged 78–95 years in Swedish RAC, including five individuals who identified within the LGBQ spectrum. A thematic reflexive analysis was conducted, drawing on Valentine’s Social geography to examine how institutional norms, peer dynamics, and spatial conditions influence residents’ opportunities to express their sexuality. Results Findings revealed three main themes: Geography of RAC: Space and Norms, Sexual Identity and Belonging and Strategies for Safety and Visibility. The results suggests that heteronormativity and perceptions of ageing shape the attitudes within RAC environments, often rendering older LGBQ adults invisible as sexual beings. The presence and attitudes of other residents were found to play an important role in shaping the space, either reinforcing exclusion or fostering belonging. LGBQ residents described employing various strategies to navigate this terrain. While some participants experienced a sense of restriction, others found ways to assert their identity and challenge dominant norms. Conclusions The study highlights that RAC is not only structured by formal policies but also co-created through everyday interactions among residents and staff. While previous research has emphasised the need for staff training and inclusive policies, these findings suggest that education alone may not be sufficient. This study argues that there may be value in establishing dedicated residential care facilities that are explicitly LGBTQ-friendly.